2023
DOI: 10.1177/10567895231158147
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the evolutionary characteristics of acoustic signals produced by granite damage under uniaxial compression

Abstract: Acoustic signals emitted during rock fracture constitute an important tool for rock damage evaluation. To investigate the evolutionary characteristics of acoustic emission (AE), microseismic (MS), and sound signals produced by hard rock fracture, uniaxial compression tests on granite specimens observed by AE, MS and sound monitoring were carried out. The evolution characteristics of the acoustic signal index, including its waveform, fractal dimension, b value, main frequency, energy proportion of signal freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Additionally, the difference in the period when accelerated growth occurs can be clearly identified (see Figure 7), that is, AE < MS < sound in order of stress level from low to high. This phenomenon arises from differences in the frequency ranges, propagation and capture routes and acquisition modes among three types of acoustic signals, which can be evidenced by the following: AE signals, characterized by high frequency, propagation and capture in rock, as well as acquisition motivated by hit parameters; MS signals, characterized by low frequency, propagation and capture in rock, and utilizing waveform flowbased acquisition; sound signals, characterized by low frequency, propagation in rock and air and capture in air, and also employing waveform flow-based acquisition (Cai et al, 2007;Su et al, 2023;Zhao G et al, 2022). Furthermore, with the increase in the intermediate principal stress σ 2 , the initial stress of activeness in each of the signals decreases, as shown in Table 2.…”
Section: Activenessmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the difference in the period when accelerated growth occurs can be clearly identified (see Figure 7), that is, AE < MS < sound in order of stress level from low to high. This phenomenon arises from differences in the frequency ranges, propagation and capture routes and acquisition modes among three types of acoustic signals, which can be evidenced by the following: AE signals, characterized by high frequency, propagation and capture in rock, as well as acquisition motivated by hit parameters; MS signals, characterized by low frequency, propagation and capture in rock, and utilizing waveform flowbased acquisition; sound signals, characterized by low frequency, propagation in rock and air and capture in air, and also employing waveform flow-based acquisition (Cai et al, 2007;Su et al, 2023;Zhao G et al, 2022). Furthermore, with the increase in the intermediate principal stress σ 2 , the initial stress of activeness in each of the signals decreases, as shown in Table 2.…”
Section: Activenessmentioning
confidence: 99%
“…Based on the experimental results, it can be concluded that in terms of the activeness, b value, main frequency and proportion of advantage frequency bands, AE, MS and sound signals exist in obvious phenomena preceding the failure of granite subjected to biaxial compression, and the similar phenomena in the three types of signals are summarized in Table 6. However, there are significant differences (see Table 7) in the precursors between AE, MS and sound signals caused by the distinctive nature of acoustic signals (e.g., frequency ranges, acquisition modes and sampling rates) (Su et al, 2021;Su et al, 2023;Zhao G et al, 2022).…”
Section: Comparison Of Precursors Between Ae Ms and Sound Signals Pro...mentioning
confidence: 99%
See 1 more Smart Citation
“…To accurately obtain abundant AE signals, the AE sensor (e.g., 1 sensor in Brazilian disc test and 2 sensors in direct shear test) was arranged as the Figures 3C, D. With reference to some studies of the rock mechanics studies using AE monitoring, the parameters of the AE system were set as shown in Table 1 (Su et al, 2020;Su et al, 2023).…”
Section: Ae Signals Acquisitionmentioning
confidence: 99%
“…At present, AE signal analysis methods can be generally categorized into two approaches: parameter-based and waveform-based analyses (Yang et al., 2021). Traditional approaches, known for their simplicity and high efficiency, are suitable for the qualitative assessment of crack development and damage evolution (Su et al., 2023). Researchers have employed various AE parameters to characterize the damage evolution process in CFRP-strengthened and reinforced concrete structures, including amplitude, energy, count, peak frequency (Nair et al., 2020; Zhang and Li, 2020).…”
Section: Introductionmentioning
confidence: 99%